Strategi Digital Marketing Bank Syariah Indonesia dan Implikasinya terhadap Inklusi Keuangan Syariah - Syf Miftahul Rahmah; Muhammad Zen; Fatmawati Fatmawati (Studia Economica : Jurnal Ekonomi Islam, 2026)
This study aims to analyze the digital marketing strategies implemented by Bank Syariah Indonesia (BSI) and examine their implications for Islamic financial inclusion in Indonesia. This research employed a qualitative approach using a library research method. Data were collected from BSI annual reports, publications of the Financial Services Authority (OJK), Bank Indonesia reports, and relevant scientific literature related to digital marketing and Islamic financial inclusion. Data were analyzed using content analysis through the processes of data reduction, categorization, interpretation, and source triangulation. The findings indicate that BSI has implemented various digital marketing strategies through social media, official websites, BSI Mobile, QRIS, BSI Agen, and Islamic financial education content. These strategies contribute to improving Islamic financial inclusion through four dimensions, namely access, usage, quality, and trust. Digital marketing expands public access to information, strengthens Islamic financial literacy, builds trust in Islamic financial services, and encourages the adoption of digital financial services. The study also proposes a conceptual model showing that digital marketing influences Islamic financial inclusion through a gradual process involving information access, literacy enhancement, trust formation, and service utilization. The findings imply that digital marketing can serve as a strategic instrument for accelerating Islamic financial inclusion and supporting the sustainable development of the Islamic finance industry in Indonesia.